Org-1 is required for the diversification of circular visceral muscle founder cells and normal midgut morphogenesis - Schaub, Christoph (2013)
The T-Box family of transcription factors plays fundamental roles in the generation of appropriate spatial and temporal gene expression profiles during cellular differentiation and organogenesis in animals. In this study we report that the Drosophila Tbx1 orthologue optomotor-blind-related-gene-1 (org-1) exerts a pivotal function in the diversification of circular visceral muscle founder cell identities in Drosophila. In embryos mutant for org-1, the specification of the midgut musculature per se is not affected, but the differentiating midgut fails to form the anterior and central midgut constrictions and lacks the gastric caeca. We demonstrate that this phenotype results from the nearly complete loss of the founder cell specific expression domains of several genes known to regulate midgut morphogenesis, including odd-paired (opa), teashirt (tsh), Ultrabithorax (Ubx), decapentaplegic (dpp) and wingless (wg). To address the mechanisms that mediate the regulatory inputs from org-1 towards Ubx, dpp, and wg in these founder cells we genetically dissected known visceral mesoderm specific cis-regulatory-modules (CRMs) of these genes. The analyses revealed that the activities of the dpp and wg CRMs depend on org-1, the CRMs are bound by Org-1 in vivo and their T-Box binding sites are essential for their activation in the visceral muscle founder cells. We conclude that Org-1 acts within a well-defined signaling and transcriptional network of the trunk visceral mesoderm as a crucial founder cell-specific competence factor, in concert with the general visceral mesodermal factor Biniou. As such, it directly regulates several key genes involved in the establishment of morphogenetic centers along the anteroposterior axis of the visceral mesoderm, which subsequently organize the formation of midgut constrictions and gastric caeca and thereby determine the morphology of the midgut.